2013
DOI: 10.1002/joc.3787
|View full text |Cite
|
Sign up to set email alerts
|

The 18.6‐year nodal tidal cycle and the bi‐decadal precipitation oscillation over the plains to the east of subtropical Andes, South America

Abstract: This work shows statistical evidence for lunar nodal cycle influence on the low‐frequency summer rainfall variability over the plains to the east of subtropical Andes, in South America, through long‐term sea surface temperature (SST) variations induced by the nodal amplitude of diurnal tides over southwestern South Atlantic (SWSA). In years of strong (weak) diurnal tides, tide‐induced diapycnal mixing makes SST cooler (warmer) together with low (high) air pressures in the surroundings of the Malvinas/Falklands… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 32 publications
(68 reference statements)
0
6
0
4
Order By: Relevance
“…Finally, since subregion V presents quasi‐cycles close to the bidecadal band, it would be interesting to explore in future works if precipitation in the subregion could be influenced by the moon nodal 18‐year cycle. In this sense, Agosta () found a bidecadal oscillation in CWA precipitation that is present all along over a 100 years of records, and the author related it with the influence of the lunar nodal cycle on the mid‐latitude lower tropospheric circulation.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, since subregion V presents quasi‐cycles close to the bidecadal band, it would be interesting to explore in future works if precipitation in the subregion could be influenced by the moon nodal 18‐year cycle. In this sense, Agosta () found a bidecadal oscillation in CWA precipitation that is present all along over a 100 years of records, and the author related it with the influence of the lunar nodal cycle on the mid‐latitude lower tropospheric circulation.…”
Section: Resultsmentioning
confidence: 99%
“…Lower (higher) SSTs over the middle (high) latitudes will weaken the SST gradient, which should result in a weakening and northward displacement of storm tracks in the westerlies as well as the midlatitude jet. Moreover, lower SSTs over the midlatitudes, associated with larger mixing in the ocean due to larger diurnal tides, may result in negative 850 hPa heights at the midlatitudes, as demonstrated for the southwestern Atlantic [ Agosta , ]. Conversely, the SST pattern (Figure ) also resembles the response to the (negative) SAM, shown to occur with a lag of 1 week with respect to atmospheric anomalies [ Ciasto and Thompson , ].…”
Section: Resultsmentioning
confidence: 99%
“…Using long‐term runs of two climate models (HadCM3 and GFDL CM2.1), they found that the 20‐year variability in the Arctic could be related to the Atlantic Multidecadal Oscillation (AMO). Agosta () found a quasi 20‐year oscillation in the summer rainfall of subtropical South America on the lee side of the Andes. Agosta () argued that this scale of variability could be linked to the lunar nodal cycle influence on the amplitude of the solar tides.…”
Section: Discussionmentioning
confidence: 99%
“…Agosta () found a quasi 20‐year oscillation in the summer rainfall of subtropical South America on the lee side of the Andes. Agosta () argued that this scale of variability could be linked to the lunar nodal cycle influence on the amplitude of the solar tides. He found a statistically significant correlation with SST variability in the vicinity of the Malvinas (Falkland) Islands.…”
Section: Discussionmentioning
confidence: 99%